2021
DOI: 10.18632/aging.203504
|View full text |Cite
|
Sign up to set email alerts
|

Association between tooth loss rate and risk of mild cognitive impairment in older adults: a population-based longitudinal study

Abstract: Mild cognitive impairment (MCI) is a symptomatic predementia phase of the trajectory of cognitive decline, and its prevalence increases with age. Although the relationship between oral health and MCI have been explored previously, it is uncertain whether individuals with different tooth loss rates have altered MCI risks. We hereby conducted a longitudinal study by using data from the Chinese Longitudinal Healthy Longevity Survey to investigate the association. Tooth loss rate was defined as the difference of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…Forty seven studies were included in this review: 24 for cognitive decline 8 , 9 , 15 , 16 , 17 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 and 23 for dementia 10 , 11 , 12 , 13 , 14 , 47 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 (Figure 1 ). Characteristics of included studies are summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty seven studies were included in this review: 24 for cognitive decline 8 , 9 , 15 , 16 , 17 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 and 23 for dementia 10 , 11 , 12 , 13 , 14 , 47 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 (Figure 1 ). Characteristics of included studies are summarized in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment of included studies is summarized in Table S2 and Supplementary Text S2 . For cognitive decline, the overall risk of bias was high; 1 study received “moderate” 56 and 23 “low” 8 , 9 , 15 , 16 , 17 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 57 , 58 , 59 , 60 for overall quality. For dementia, overall risk of bias was moderate; 2 studies receiving “good,” 67 , 70 9 “moderate” 10 , 13 , 14 , 64 , 68 , 71 , 72 , 74 , 77 and 12 “low” 11 , 12 , 47 , 61 , 62 , 63 , 65 , 66 , 69 , 73 , 75 , 76 for overall quality.…”
Section: Resultsmentioning
confidence: 99%
“…Similar association between tooth loss and cognitive impairment has also been demonstrated by several other epidemiological studies. 10 21 In addition, a recently published retrospective study based on two USA national health surveys reported that edentulism was highly associated with cognitive decline, and that there was a gradient effect between a decreasing number of teeth and an increasing risk of cognitive impairment. 22 Another recent study of national database from Japan reported that older people with fewer teeth were more likely to develop Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Highly sedentary humans (≥8 h/day) display reduced hippocampal volumes and increased white matter (WM) hyperintensities [ 3 , 4 ] that are associated with accelerated cognitive, neuropsychiatric and functional decline [ 5 ]. In addition to the changes associated with a sedentary life, it has become clear that oral dysfunction is present in the same individuals and that this group feature is also associated with dementia or mild cognitive decline [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. While it is not clear whether poor oral health predicts dementia, substantial data suggests that oral health declines as cognitive impairment and dementia progresses [ 7 , 12 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that masticatory exercise improves cognitive function in older adults [ 17 ] and thus the link between cognitive decline and masticatory dysfunction is now clear [ 8 , 18 , 19 , 20 , 21 , 22 ]. As loss of masticatory activity [ 8 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 ] and sedentary life style [ 23 , 24 ] are risk factors for age-related cognitive decline, there is a need to focus attention on those sub-populations that experience greater oral health deterioration or impairment of the stomatognathic system, and those having living sedentary lives.…”
Section: Introductionmentioning
confidence: 99%